Socioscientific Issue-Based Decision Making at Elementary School: Bibliometric Analysis - Rahayu, Galih Dani Septiyan; Maftuh, Bunyamin; Sapriya; Sopandi, Wahyu (Indonesian Journal of Educational Research and Review, 2024)
Decision making is a very important ability possessed by individuals at this time, especially in solving socio-scientific issues. The purpose of this study was to analyze research trends regarding socio-scientific issue-based decision making in elementary schools by conducting a bibliometric analysis of bibliographic data on technical research articles indexed by Google Scholar by combining analysis in terms of bibliometric map distribution using VOS viewer software. The research data was obtained from Google Scholar database through the Publish or Perish reference management application. The data filtering process was carried out based on the keywords "decision making and socio-scientific issues" contained in the topic, title, keywords, and abstract domains. The tracing was carried out on articles published from 2006 to 2022. From the search results obtained 23 relevant articles. The results showed that research on decision making based on socio-scientific issues was mostly carried out in 2010 and 2014. Research on decision making based on socio-scientific issues was rarely carried out at the elementary school level. So, it can be concluded that the opportunity for developing research regarding decision-making based on socio-scientific issues at the elementary school level is very large. Therefore, it is hoped that this study can provide references and considerations in seeking further research fields, especially those related to decision-making based on socio-scientific issues in elementary schools.